Association between vitamin K intake and depressive symptoms in US adults: Data from the National Health and Nutrition Examination Survey (NHANES) 2013–2018 - Zhang, Yuyi; Tan, Weiliang; Xi, Xiaolan; Yang, Hui; Zhang, Ke; Li, Shengnan; Chen, Xuefen; Zuo, Hui (Frontiers in Nutrition, 2023)
Background The relationship between vitamin intake and depression has attracted increasing attention. However, several studies examining such relationship among populations at different age groups have produced inconsistent findings. This study was aimed to investigate the cross-sectional association between vitamin K intake and depressive symptoms in US adults. Methods We used the data from a nationally representative sample of 11,687 adults from the 2013 to 2018 National Health and Nutrition Examination Survey (NHANES). Vitamin K intake was assessed by the 24-h dietary recall at the first day. Depressive symptoms were assessed using the 9-item Patient Health Questionnaire (PHQ-9). Logistic regression and generalized additive model were used to examine the association between vitamin K intake and depressive symptoms. Results The weighted prevalence of depressive symptoms was 10.2% (8.0% in men and 12.0% in women). We observed a significant inverse linear relationship between vitamin K intake and depressive symptoms in models adjusted for age, sex, race/ethnicity, marital status, educational status, family poverty income ratio (PIR), home status, body mass index (BMI), smoking status, physical activity, sleep disorders, hypertension, hyperlipidemia, and diabetes. The odds ratios (OR) (95% CI) for the highest compared with the lowest quartile of vitamin K intake was 0.68 (95% CI: 0.52, 0.89, p-trend < 0.05). The association was similar in subgroups stratified by age, sex, race/ethnicity, marital status, educational status, PIR, home status, BMI, smoking status, physical activity, sleep disorders, hypertension, hyperlipidemia, and diabetes. Conclusion Vitamin K intake was inversely and independently associated with the odds of depressive symptoms in the US adults. Prospective studies are warranted to confirm our findings.